THE ROLE OF THE ALT ENZYME IN THE UNUSABILITY OF PREPARED DONOR BLOOD - Saidov A.B.; Umarov D.R.; Madolimov A. M.; Usmanova Z. I. (Galaxy International Interdisciplinary Research Journal, 2023)
In the Republican Blood Transfusion Center, the blood components that were destroyed due to the high level of ALT enzyme during the last 5 years were analyzed. The results showed that 4% of the blood prepared from donors was discarded because of high ALT enzyme. An increase in the ALT enzyme index is relatively more common in winter and spring than the annual average, and on the contrary, it is less common in summer and autumn.